ANIME DAN TEKNOLOGI ANIMASI - Baruna, Bayu (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
Anime is a term that represents Japanese animation, an important part of Japanese culture, and also a popular entertainment throughout the world. Although getting influenced by Walt Disney's animation, anime has it’s own specific characteristics that animation does not have in general. Especially in terms of genre variations, visual and storytelling quality. Furthermore, Japanese society considers manga visual and storytelling to be a form of art. Since some anime are adaptations of manga, it can be said that the spirit of art also merges into the anime. This paper aims to see the spirit of art move hand in hand with the development of increasingly sophisticated animation technology every day.